Compatibilizer for bioasphalt composition

The introduction of a lignin derivative compound as a compatibilizing agent in bioasphalt compositions addresses the compatibility and stability issues between lignin and asphalt, resulting in improved physical properties and reduced viscosity.

JP2025063866APending Publication Date: 2025-04-16NIPPON PAPER IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024174095
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-10-03
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing bioasphalt compositions face challenges in improving the compatibility and stability between lignin and asphalt, which affects the physical properties of the asphalt.

Method used

A compatibilizing agent is introduced, comprising a lignin derivative compound with specific structural units derived from lignin and aromatic water-soluble compounds, enhancing the compatibility between lignin and asphalt.

Benefits of technology

The compatibilizing agent improves the compatibility and reduces the viscosity of the bioasphalt composition, thereby enhancing the physical properties of the asphalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063866000003
    Figure 2025063866000003
  • Figure 2025063866000001
    Figure 2025063866000001
  • Figure 2025063866000002
    Figure 2025063866000002
Patent Text Reader

Abstract

To provide a compatibilizer for bioasphalt compositions that is capable of enhancing the compatibility between a lignin component and asphalt in the bioasphalt compositions.SOLUTION: The present invention provides a compatibilizer for a bioasphalt composition, comprising a lignin derivative compound that includes: structural unit (I): a structural unit derived from a lignin-based compound, and structural unit (II): a structural unit derived from an aromatic water-soluble compound including at least an aromatic water-soluble compound having an alkylene oxide chain, and a bioasphalt composition comprising asphalt, a lignin component such as kraft lignin, and the compatibilizer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an additive for a bioasphalt composition. [Background technology]

[0002] Asphalt is widely used for paving the ground such as roads, and attempts are being made to produce bioasphalt by adding lignin to asphalt. Patent Document 1 describes that the lignin-containing material and asphalt-containing material can be dispersed even after cooling by adding a surfactant to the material and mixing it and stirring it while heating it to 120°C to 250°C. Patent Document 2 describes that the stability of the resulting mixture is improved by mixing lignin and asphalt at or below the glass transition temperature of lignin.

[0003] On the other hand, Patent Document 3 describes that a lignin derivative compound, which is a reaction product between a lignin sulfonic acid compound and a water-soluble aromatic compound, exhibits high dispersibility in cement, gypsum, and the like. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-195433 A [Patent Document 2] WO 2022 / 85641 [Patent Document 3] Patent No. 7154217 Summary of the Invention [Problem to be solved by the invention]

[0005] As described in Patent Documents 1 and 2, improving the dispersibility and stability of bioasphalt is an issue, and there is a problem in that it is difficult to obtain the effect of improving the physical properties of asphalt by adding lignin. Furthermore, Patent Document 3 does not disclose the combination of a lignin derivative compound with an asphalt composition.

[0006] An object of the present invention is to provide a compatibilizer for a bioasphalt composition that can improve the compatibility between a lignin component and asphalt in the bioasphalt composition. [Means for solving the problem]

[0007] The present invention provides the following [1] to [6]. [1] A compatibilizer for a bioasphalt composition comprising a lignin derivative compound containing the following structural units (I) and (II): (I): Structural units derived from lignin compounds (II): A structural unit derived from an aromatic water-soluble compound that contains at least an aromatic water-soluble compound having an alkylene oxide chain. [2] The agent according to [1], wherein the aromatic water-soluble compound having an alkylene oxide chain includes an aromatic water-soluble compound having an alkylene oxide chain with an average added mole number of 25 or more of alkylene oxide. [3] The agent according to [1] or [2], wherein the weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is 1 / 99 to 99 / 1. [4] A bioasphalt composition comprising asphalt, kraft lignin, and the agent according to any one of [1] to [3]. [5] The composition according to [4], wherein the content of the agent according to any one of [1] to [3] is 0.05 to 10% by weight based on 100% by weight of the bioasphalt composition. [6] A method for producing the bioasphalt composition according to [4] or [5], comprising a step of premixing the agent according to any one of [1] to [3] with kraft lignin and mixing the premix with a raw material containing asphalt in a heated and molten state. Effect of the Invention

[0008] The compatibilizer for a bioasphalt composition of the present invention can improve the compatibility between the lignin component and asphalt in the bioasphalt composition, and can reduce the viscosity of the bioasphalt composition. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is an image of a GPC chart (UV detection wavelength: 280 nm) of a lignin derivative compound for explaining the peak area ratio of high molecular weight components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [1. Compatibilizer for bio-asphalt] The compatibilizer for bioasphalt contains the following lignin derivative compound as an active ingredient.

[0011] [1.1 Building blocks of lignin derivative compounds] The lignin derivative compound is a polymer containing at least the structural units (I) and (II). Since lignin, which is the main skeleton of the structural unit (I), has a very complicated molecular structure, it is difficult to uniformly specify the chemical structure of the lignin derivative compound by a general formula or the like.

[0012] -Structural unit (I)- The structural unit (I) is a structural unit derived from a lignosulfonic acid compound. Lignosulfonic acid compounds are compounds that have a skeleton in which the carbon at the α-position of the side chain of the hydroxyphenylpropane structure of lignin is cleaved to introduce a sulfo group (sulfonic acid group). The structure of the skeleton is shown in formula (1). [ka]

[0013] The lignosulfonic acid compound may be a modified product of a compound having the skeleton represented by the above formula (1) (hereinafter, also referred to as a "modified lignosulfonic acid compound"). The modification method is not particularly limited, and examples thereof include chemical modification methods such as hydrolysis, alkylation, alkoxylation, sulfonation, sulfonate esterification, sulfomethylation, aminomethylation, and desulfonation; and a method of molecular weight fractionation of a lignosulfonic acid compound by ultrafiltration. Among these, the chemical modification method is preferably one or more modification methods selected from hydrolysis, alkoxylation, desulfonation, and alkylation.

[0014] The lignosulfonic acid compound may be in the form of a salt. Examples of the salt include monovalent metal salts, divalent metal salts, ammonium salts, and organic ammonium salts. Among these, calcium salts, magnesium salts, sodium salts, and mixed calcium-sodium salts are preferred.

[0015] A lignin sulfonate compound usually has at least one functional group site capable of reacting with the aromatic water-soluble compound constituting the structural unit (II). Examples of such sites include a carboxyl group, a hydroxyl group (phenolic hydroxyl group, alcoholic hydroxyl group), a thiol group, a sulfo group, an aromatic ring, an ether bond, and an alkyl chain. In one embodiment, the functional group site of the lignin sulfonate compound is bonded directly or via a condensing agent such as formaldehyde with the aromatic water-soluble compound to form a lignin derivative compound.

[0016] The method of producing the lignosulfonic acid compound and its origin are not particularly limited, and it may be either a natural product or a synthetic product. Lignosulfonic acid compounds are one of the main components of the waste liquor of sulfite pulp obtained by cooking wood under acidic conditions. Therefore, lignosulfonic acid compounds derived from sulfite pulp waste liquor may be used.

[0017] -Structural unit (II)- The structural unit (II) is a structural unit derived from a water-soluble aromatic compound. The aromatic water-soluble compound means a compound that contains at least one aromatic skeleton and is water-soluble. The aromatic water-soluble compound is preferably a compound that can bond with a functional group contained in a lignosulfonic acid compound by chemical reaction, and more preferably a compound that can react with a functional group contained in a lignosulfonic acid compound as a main component of sulfite pulp waste liquor. The type of chemical reaction is not particularly limited, and examples thereof include radical reaction, ionic bond, coordinate bond, condensation reaction, reaction involving hydrolysis, reaction involving dehydration, reaction involving oxidation, reaction involving reduction, and reaction involving neutralization.

[0018] The aromatic water-soluble compound preferably has an alkylene oxide chain or a polar group. This can improve the reactivity when forming a bond between the structural units (I) and (II). The polar group may be an ionic functional group, such as a carboxyl group, a hydroxyl group, a sulfo group, a nitroxyl group, a carbonyl group, a phosphate group, an amino group, or an epoxy group. Anionic functional groups such as a hydroxyl group, a carboxyl group, a sulfo group, or a phosphate group are preferred, and a carboxyl group or a sulfo group is more preferred. The anionic functional group in the lignin derivative compound can be quantitatively and qualitatively observed by instrumental analysis such as NMR or IR.

[0019] Examples of the aromatic water-soluble compound include the following compounds.

[0020] (Water-soluble aromatic compounds having alkylene oxide chains) The number of carbon atoms of the alkylene oxide unit constituting the alkylene oxide chain (group) is not particularly limited, and is usually 2 to 18, preferably 2 to 4, and more preferably 2 to 3. Examples of the alkylene oxide unit include an ethylene oxide unit, a propylene oxide unit, and a butylene oxide unit, and an ethylene oxide unit or a propylene oxide unit is preferred. The average number of moles of the alkylene oxide unit added is usually 20 or more or 25 or more, preferably 30 or more, and more preferably 35 or more. This allows compatibility with asphalt to be stably exhibited. The upper limit is preferably 300 or less, more preferably 200 or less, and even more preferably 150 or less. This allows compatibility to be stably exhibited. Therefore, the average number of moles added is preferably 20 to 300, or 25 to 300, more preferably 30 to 200, and even more preferably 35 to 150. The above-mentioned average number of moles added is a guideline, and regardless of whether the above-mentioned range is satisfied, the alkylene oxide chain may contain one in which alkylene oxide units are not repeatedly added (monoalkylene oxide group).

[0021] The polyalkylene oxide chain may be composed of one type of alkylene oxide group or two or more types of alkylene oxide groups. The addition form of each alkylene oxide group in the polyalkylene oxide chain composed of two or more types of alkylene oxide groups may be any of random, block, and mixture thereof. The terminal unit of the polyalkylene oxide chain is usually a hydroxyl group, but is not limited thereto, and may be an alkyl ether or a carboxylate ester as long as it does not interfere with the bond with the lignin sulfonic acid compound.

[0022] Examples of aromatic water-soluble compounds having an alkylene oxide chain include oxyalkylene group adducts to aromatic compounds such as phenol, cresol, nonylphenol, naphthol, methylnaphthol, butylnaphthol, bisphenol A, and bisphenol S. More specifically, examples include polyalkylene oxide alkylphenyl ethers, polyalkylene oxide phenyl ethers, polyalkylene oxide alkylnaphthyl ethers, and polyalkylene oxide naphthyl ethers. Among these, benzene ring derivatives are preferred because they can have good co-condensation properties, and at least one of polyalkylene oxide alkylphenyl ethers and polyalkylene oxide phenyl ethers is more preferred, and polyalkylene oxide phenyl ethers (particularly, oxyalkylene group adducts to phenol) (for example, poly(ethylene oxide) monophenyl ether, poly(propylene oxide) monophenyl ether, and the preferred range of the average added mole number of ethylene oxide unit and propylene oxide unit is as described above) are even more preferred. The aromatic water-soluble compound having an alkylene oxide chain may be used alone or in combination of two or more kinds.

[0023] (Aromatic water-soluble compounds having a carboxyl group) Examples of aromatic water-soluble compounds having a carboxyl group include naphthalene ring or benzene ring derivatives having at least one carboxyl group. More specifically, examples include isophthalic acid, oxynaphthoic acid, benzoic acid, hydroxybenzoic acid, and isomers thereof. Because of good reactivity, o-hydroxybenzoic acid, m-hydroxybenzoic acid, and p-hydroxybenzoic acid are preferred, and p-hydroxybenzoic acid is more preferred. The aromatic water-soluble compounds having a carboxyl group may be one type or a combination of two or more types.

[0024] (Water-soluble aromatic compounds having sulfo groups) Examples of aromatic water-soluble compounds having a sulfo group include alkylnaphthalenesulfonic acid, alkylphenolsulfonic acid, aniline sulfonic acid, and alkylbenzenesulfonic acid. More specifically, examples of aromatic water-soluble compounds include naphthalenesulfonic acid, methylnaphthalenesulfonic acid, butylnaphthalenesulfonic acid, phenolsulfonic acid, cresolsulfonic acid, aniline sulfonic acid, benzenesulfonic acid, toluenesulfonic acid, and their isomers and condensates. Examples of condensates include naphthalenesulfonic acid-formaldehyde condensates. Because of their good reactivity, phenol derivatives and aniline sulfonic acid having a sulfo group are preferred, phenolsulfonic acid and aniline sulfonic acid are more preferred, and aniline sulfonic acid is even more preferred. The aromatic water-soluble compounds having a sulfo group may be one type or a combination of two or more types.

[0025] (Other aromatic water-soluble compounds) The other aromatic water-soluble compounds include aromatic water-soluble compounds having no alkylene oxide chain, carboxyl group, or sulfo group, such as (alkyl)phenols such as phenol and cresol. The other aromatic water-soluble compounds may be one type or a combination of two or more types.

[0026] The aromatic water-soluble compound contains at least an aromatic water-soluble compound having an alkylene oxide chain, and it is more preferable to use only an aromatic water-soluble compound having an alkylene oxide chain, or a combination of said compound with an aromatic water-soluble compound having a carboxyl group and / or an aromatic water-soluble compound having a sulfo group.

[0027] The structural unit (II) may be a structural unit derived from one type of aromatic water-soluble compound, or may be a structural unit derived from two or more types. The aromatic water-soluble compound may be a single type or a combination of two or more types, and is preferably an aromatic water-soluble compound having an alkylene oxide chain alone, or a combination of the compound with an aromatic water-soluble compound having a carboxyl group and / or an aromatic water-soluble compound having a sulfo group.

[0028] -Other structural units (III)- The lignin derivative compound may have a structural unit (III) other than the structural units (I) and (II). For example, aromatic compounds other than aromatic water-soluble compounds (e.g., simple aromatic hydrocarbon compounds such as benzene and naphthalene), (poly)alkylene glycol alkenyl ether compounds; water-soluble polyalkylene glycols having hydrogen atoms at both ends, polyoxyalkylene compounds, polycarboxylic acid compounds, and polyester compounds, each of which may be derived from a structural unit (e.g., the polymer block described in WO 2018 / 56124). The structural unit (III) may be one type or a combination of two or more types.

[0029] [1.2 Composition ratio of each structural unit of lignin derivative compound] The weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is usually 1 / 99 to 99 / 1, preferably 2 / 98 to 90 / 10, more preferably 5 / 95 to 70 / 30 or 10 / 90 to 70 / 30, and even more preferably 15 / 85 to 70 / 30 or 20 / 80 to 60 / 40 (the total of (I) and (II) being 100% by weight).

[0030] When the structural unit (III) is contained, the weight proportion thereof is usually 5% by weight or less, preferably 3% by weight or less, and more preferably 2% by weight or less, relative to 100% by weight of the total of (I) and (II).

[0031] (I) / (II) is defined as (weight of solids of lignosulfonic acid compound before reaction) / (weight of solids of aromatic water-soluble compound before reaction) in the reaction between a lignosulfonic acid compound and a water-soluble aromatic compound, and is measured by this method in the examples described later.

[0032] When the structural unit (II) contains a structural unit derived from a compound other than an aromatic water-soluble compound having an alkylene oxide chain, the ratio of the structural unit derived from an aromatic water-soluble compound having an alkylene oxide chain in the structural unit (II) is usually 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. There is no particular upper limit, and it is sufficient if it is 100% by weight or less.

[0033] The weight ratio of each of the above constituent units corresponds to the ratio of each compound as a raw material used at the start of the reaction.

[0034] [1.3 Salts of lignin derivative compounds] The lignin derivative compound may be any reaction product obtained by the above-mentioned reaction, and may be either a free acid or a neutralized salt thereof. Neutralized salts are preferred because the polymer is easy to store and use. Examples of neutralized salts of the reaction product include alkali metal salts such as sodium salts or potassium salts; alkaline earth metal salts such as calcium salts; ammonium salts; and salts of organic amines.

[0035] [1.4 Physical properties of lignin derivative compounds] The lignin derivative compound preferably has the following physical properties.

[0036] -Weight average molecular weight- The weight-average molecular weight of the lignin derivative compound is not particularly limited, but is preferably 1,000 to 500,000, more preferably 2,000 to 300,000, and further preferably 5,000 to 200,000. The weight-average molecular weight in the present invention can be measured by a known method using gel permeation chromatography (GPC) in terms of polyethylene glycol.

[0037] The GPC measurement conditions are exemplified as follows. The values ​​measured in the examples below are also measured under these conditions. Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh or GL Science) Detector: Differential refractometer (manufactured by Tosoh)

[0038] -Peak area ratio of polymer components- The peak area ratio of the high molecular weight component of the lignin derivative compound is usually 80% or more, preferably 85% or more. The upper limit is 99% or less, more preferably 97% or less. By being within this range, the structural units (I) and (II) in the lignin derivative compound are present in a well-balanced manner, the compatibility with asphalt is further improved, and the effect of improving physical properties such as viscosity reduction of the asphalt composition can be exhibited well. In this specification, the peak area ratio of the high molecular weight component means the ratio of the peak area value of the component having a weight average molecular weight of 1,200 or more to the peak area of ​​all components in the chart when UV (detection wavelength 280 nm) is used in the gel permeation chromatography (GPC) measurement of the lignin derivative compound, and can be calculated by the following formula. Peak area ratio of high molecular weight components = (area value of high molecular weight components in GPC chart (280 nm)) / (area value of all components in GPC chart (280 nm)) The detector is not particularly limited, but an example thereof is an ultraviolet absorption detector (manufactured by Tosoh Corporation).

[0039] The method of specifying each area value will be described with reference to the GPC chart in FIG. 1. In FIG. 1, point (1) is the elution start point, point (2) is the elution end point, and point (3) is the value corresponding to a weight average molecular weight of 1,200. The area value of the high molecular weight component in the above formula is the intersection of the line (baseline: dotted line in FIG. 1) connecting point (1) and point (2). The area value of all components means the area of ​​the part surrounded by the line (baseline: dotted line in FIG. 1) connecting point (1) and point (2) and the curve from point (1) to point (2). The peak area value of a component having a weight average molecular weight of 1,200 or more means the area of ​​the part surrounded by the part of the baseline from point (1) to point (3), the straight line (dash line in FIG. 1) extending perpendicularly from point (3) to the baseline, and the curve. The measurement conditions of GPC can be the same as those of GPC when measuring the weight average molecular weight described above.

[0040] -Thermogravimetric reduction rate- The lower limit of the thermal weight loss rate of the lignin derivative compound is usually 50% or more, preferably 55% or more, and more preferably 60% or more. When it is 50% or more, the ash content is low, and the inhibition of the effect of the present invention due to inevitable impurities other than the lignin derivative compound is suppressed, and a good effect can be ensured. The upper limit is 85% or less, preferably 80% or less, and more preferably 75% or less. When it is 85% or less, heat resistance can be ensured. Therefore, the thermal weight loss rate measured by TG-DTA is 50 to 85%, preferably 55 to 80%, and more preferably 60 to 75%. When a granular material containing a lignin derivative compound is used as a compatibilizer for a bioasphalt composition, it is preferable to satisfy the above thermal weight loss rate.

[0041] -Thermal decomposition point- The lower limit of the thermal decomposition point of the lignin derivative compound is preferably 350 ° C or more, more preferably 360 ° C or more, and even more preferably 370 ° C or more. If it is 350 ° C or more, heat resistance can be ensured. The upper limit is less than 400 ° C, preferably 398 ° C or less, more preferably less than 395 ° C or 394 ° C or less. If it is less than 400 ° C, resinification of the granular composition is suppressed and it can function as a compatibilizer. Therefore, the thermal decomposition point measured by TG-DTA is preferably 350 ° C or more and less than 400 ° C, more preferably 360 to 398 ° C, and even more preferably 370 to less than 395 ° C or 394 ° C or less. When a granular material containing a lignin derivative compound is used as a compatibilizer for a bioasphalt composition, it is preferable to satisfy the above-mentioned thermal weight loss rate.

[0042] The thermal decomposition point and the thermal weight loss rate can be measured using a thermogravimetric differential calorimeter (TG-DTA). An example of the case of a granular material is as follows. A granular composition of 10 g of a granular material of a lignin derivative compound sample (which may contain compounds (i) and (ii)) is dried and solidified to prepare a sample. The drying and solidification method includes 1) a method of drying and solidifying at 105°C for one day using a dryer (product name "Air-blowing constant temperature incubator DKM600", manufactured by Yamato Scientific Co., Ltd.), 2) a method of drying and solidifying at -20°C for one day using a freeze dryer (product name "FDU-1200", manufactured by Tokyo Rika Kikai Co., Ltd.), 3) a method of drying and solidifying at 180°C using a spray dryer (for example, product name "TR120", manufactured by Priss Co., Ltd.), and 4) a method of using a drum dryer (for example, manufactured by Katsuragi Kogyo Co., Ltd.). Then, about 10 mg of the solidified sample is heated from 50°C to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere. The temperature at which the weight loss rate of the sample is at its maximum is taken as the thermal decomposition point, and the weight loss rate up to 600°C is taken as the thermal weight loss rate. The measurement is performed three times for each sample, and the average value is taken as the average value.

[0043] -Average particle size- When a granular material containing a lignin derivative compound is used as a compatibilizer for a bioasphalt composition, the average particle size is preferably 30 μm or more. The upper limit is preferably 250 μm or less. The average particle size is the value at which the accumulated distribution is 50% when the molecular weight distribution obtained by measuring 3 g of a powder sample under dry conditions using a laser diffraction particle size distribution measuring device (Mastersizer 3000 (Malvern)) is expressed as particle size (μm) on the horizontal axis and volume (%) on the vertical axis.

[0044] -surface tension- When a liquid containing a lignin derivative compound is used as a compatibilizer for a bioasphalt composition, the surface tension in a solution form with a non-volatile content of 10% at 100°C is preferably 25 dyne / cm or more, more preferably 27 dyne / cm or more, and even more preferably 29 dyne / cm or more. The upper limit is preferably 55 dyne / cm or less, more preferably 50 dyne / cm or less, and even more preferably 45 dyne / cm or less. The definition of "non-volatile content at 100°C" is the same as that in B-type viscosity. "Solution form with a non-volatile content of 10%" refers to an aqueous solution with a non-volatile content concentration of the lignin derivative of 8 to 12%. The surface tension can be measured with a surface tensiometer (for example, CBVP-A3 manufactured by Kyowa Interface Science Co., Ltd.).

[0045] The above physical properties can be adjusted by appropriately adjusting the types and amounts of the lignosulfonic acid compound, the water-soluble compound, and the lignin derivative. In particular, when a lignin derivative is included, the properties can be adjusted by appropriately designing the reaction conditions of the lignin derivative. More specifically, the properties can be adjusted by appropriately changing the type and amount of the reaction initiator, the concentration of the reaction solution, the ratio of the lignosulfonic acid compound to the water-soluble compound, the type and amount of the side chain functional group of the water-soluble compound, the reaction temperature, the reaction time, etc.

[0046] [1.5 Method for producing lignin derivative compound] The preparation of the lignin derivative compound may be a method of reacting raw material compounds including a lignin sulfonic acid compound (hereinafter sometimes referred to as compound (i)) and an aromatic water-soluble compound (hereinafter sometimes referred to as compound (ii)). For example, a method of reacting a lignin sulfonic acid compound with an aromatic water-soluble compound can be mentioned. In detail, for example, a method of condensing (e.g., formaldehyde condensation) an aromatic water-soluble compound with a lignin sulfonic acid compound, a radical reaction, or an ionic bond can be mentioned. For example, a method of formaldehyde condensation can be mentioned, for example, a method of adding formaldehyde to a lignin sulfonic acid compound and bonding it with an aromatic water-soluble compound. For example, a method of radical reaction can be mentioned, for example, a method of extracting hydrogen radicals by acting a radical initiator on a lignin sulfonic acid compound, and radical reacting the generated radical with at least one kind of aromatic water-soluble compound.

[0047] The method for producing the lignosulfonic acid compound as the raw material is not particularly limited, and for example, it can be produced by a method of extracting it from the waste liquid of sulfite pulp obtained by cooking wood under acidic conditions. Furthermore, a powdered processed product that has been subjected to a drying process such as a powder drying process may also be used. Being in powder form makes it easy to handle.

[0048] The lignin sulfonic acid compound may be a commercially available product, for example, Vanilex HW (manufactured by Nippon Paper Industries Co., Ltd.), Sunex M (manufactured by Nippon Paper Industries Co., Ltd.), Pearlex NP (manufactured by Nippon Paper Industries Co., Ltd.), or Sunflow RH (manufactured by Nippon Paper Industries Co., Ltd.) The lignin sulfonic acid compound may be in the form of a salt such as a monovalent metal salt, a divalent metal salt, an ammonium salt, or an organic ammonium salt (preferably a monovalent metal salt or a divalent metal salt, more preferably a calcium salt, a magnesium salt, a sodium salt, or a mixed calcium-sodium salt).

[0049] The reaction temperature between the lignosulfonic acid compound and the aromatic compound may be appropriately set depending on the solvent used, and is not particularly limited, but is usually 0 to 200° C., and preferably 45 to 150° C. When a low-boiling compound is used as the reaction solvent, it is preferable to carry out the reaction under pressure using an autoclave in order to improve the reaction rate.

[0050] The reaction form of the lignosulfonic acid compound and the aromatic water-soluble compound may be either a solution reaction or a bulk reaction. In the case of a solution reaction, a solvent may be used. Examples of the solvent include water; alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as cyclohexane and n-hexane; esters such as ethyl acetate; ketones such as acetone and methyl ethyl ketone; and cyclic ethers such as tetrahydrofuran and dioxane. Among them, at least one of water and lower alcohols is preferred, and water is more preferred. This can improve the solubility of the raw material monomer and the resulting copolymer, and can omit the desolvation process. The solvent may be used alone or in combination of two or more (for example, a water-alcohol mixed solvent).

[0051] A defoaming agent may be used during the preparation of the lignin derivative. This makes it possible to suppress foaming during the reaction and to build a uniform reaction system. Examples of the defoaming agent include those containing a nonionic surfactant as an active ingredient.

[0052] The reaction conditions for preparing the lignin derivative compound can be adjusted as necessary. The progress of the reaction is characterized by a clear increase in viscosity. When the desired viscosity is reached, the reaction can be stopped by cooling or neutralization.

[0053] In the preparation of the lignin derivative compound, the addition of water may be adjusted to control the condensation viscosity and the condensation time. The pH during the reaction may be adjusted to an appropriate value. The reaction is usually carried out under acidic conditions. When the reaction system is already acidic due to the aromatic compound having a sulfo group and the unreacted acid contained therein, the reaction may be carried out in the acidic region as it is. When the reaction system is not acidic, the reaction may be carried out by adding an acid catalyst such as hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, or p-toluenesulfonic acid in advance. The preferred acid is sulfuric acid, but may be other than the above specific examples and is not limited thereto.

[0054] The reaction rate of the aromatic water-soluble compound is preferably 30% or more, more preferably 40% or more, and further preferably 50% or more. When the reaction rate is 50% or more, the compatibilizing effect can be satisfactorily exhibited.

[0055] The reaction rate of the aromatic water-soluble compound can be measured as follows, and is measured in the examples described below. First, in the GPC measurement, when UV (detection wavelength 280 nm) is used, the peak areas before and after the reaction are compared. Next, when the peak area before the reaction (i.e., the peak area of ​​the peak corresponding to the aromatic water-soluble compound) is [b] and the peak area after the reaction is [a], the reaction rate can be calculated by the formula: ([b]-[a]) / [b]. The GPC measurement conditions can be the same as those for the GPC conditions used in the above-mentioned weight average molecular weight measurement.

[0056] If necessary, the reaction solution after the condensation reaction may be subjected to post-treatment such as heat treatment at a temperature of 60 to 120° C. under a pH condition of 8.0 to 13.0, neutralization treatment, or treatment of adjusting the pH of the reaction solution (for example, lowering to 1.0 to 4.0, preferably 1.5 to 2.0) to precipitate the reaction product as a solid. The post-treatment is usually performed continuously for about 10 minutes to 3 hours. This can significantly reduce the aldehyde content (for example, formaldehyde content) of the reaction solution. In addition to or instead of the removal of free formaldehyde by the so-called Cannizzaro reaction described above, other methods for reducing excess formaldehyde, for example, known in the field of melamine-formaldehyde resin and phenol-formaldehyde resin chemistry, may be used. Examples of such methods include the addition of a formaldehyde absorbent (addition of a small amount of sodium hydrogen sulfite, addition of hydrogen peroxide).

[0057] In the case of a treatment in which the pH of the reaction solution is adjusted to precipitate the reaction product as a solid, the supernatant salt solution is then separated and removed, and the remaining mostly salt-free free reaction product is redissolved in an amount of water sufficient to obtain the desired solid concentration, thereby obtaining the lignin derivative.

[0058] The neutralization treatment can be carried out using a neutralizing agent capable of neutralizing the reaction product and the catalyst. Examples of the neutralizing agent include basic compounds such as sodium hydroxide, calcium hydroxide, Ba(OH)2, and the like (including salts and hydroxides thereof). As a result, calcium sulfate and barium sulfate, which are less soluble, are formed together with free sulfuric acid, and precipitate in the form of gypsum, etc. Therefore, the precipitate can be separated and removed by subsequent filtration, and a salt-free polymer can be obtained. Furthermore, undesirable sodium sulfate may be separated and removed by dialysis or ultrafiltration.

[0059] In the case where by-products such as sodium sulfate, calcium sulfate, and hydrates thereof are generated in the addition and neutralization of the basic compound, it is preferable to add the basic compound in a heated state after the reaction and maintain the heated state to improve the removal of the by-products. The heating is preferably performed to 40° C. or higher. The time for maintaining the heated state is preferably 30 minutes or more. The concentration, pH, etc. of the obtained lignin derivative compound may be adjusted as necessary after the reaction is completed.

[0060] [1.6 Optional components] The bioasphalt compatibilizer may contain optional components other than the lignin derivative compound, such as anti-peeling components other than the copolymer, solvents, antioxidants, heat stabilizers, light stabilizers, UV absorbers, flame retardants, plasticizers, pigments, dyes, dye dispersants, chelating agents, and unreacted compounds (i) and (ii).

[0061] [1.7 Dosage form] The formulation of the bioasphalt compatibilizer is not particularly limited. For example, it may be granular (solid such as powder or pellet) or liquid (including gel). Examples of methods for forming into granules include a method of drying a lignin derivative compound (including optional components as necessary). Examples of drying methods include a method of neutralizing with a hydroxide of a divalent metal such as calcium or magnesium to form a polyvalent metal salt and then drying; a method of supporting the compound on an inorganic powder such as silica-based fine powder and drying; a method of drying and solidifying the compound into a thin film on a support of a drying device (for example, a drum-type drying device, a disk-type drying device, or a belt-type drying device); and a method of drying and solidifying the compound using a spray dryer. Among these, a drying method using a drying device is preferred, and a drying method using a disk-type drying device or a drum-type drying device is more preferred. A method of using a grinding device after drying with a drying device may also be used. This makes it easier to adjust the particle size, and by adjusting the particle size to a predetermined size (for example, 250 μm or less), the compound may be more easily blended into asphalt. The grinding device is not particularly limited, but examples thereof include a hammer mill, a pin mill, a rotary mill, a vibration mill, a roller mill, a cutter mill, etc. On the other hand, examples of the method for preparing a liquid include a method in which the above-mentioned drying treatment is not performed after the preparation of the lignin derivative compound, and a method in which the above-mentioned drying treatment is performed, and then the lignin derivative compound is dissolved in an arbitrarily selected solvent and stirred as necessary to prepare a solution, suspension, dispersion, or gel.

[0062] [2. Compatibilizer for bioasphalt composition] The lignin derivative compound can be used as a compatibilizer for bioasphalt because the addition of the lignin derivative compound to bioasphalt can provide a compatibilizing effect between the asphalt and lignin components contained in the bioasphalt.

[0063] [2.1 Bioasphalt composition] The bioasphalt composition is an asphalt composition (asphalt mixture, asphalt mixture) that contains a lignin component such as kraft lignin.

[0064] The bioasphalt composition is usually used in at least one of the surface and base layers of asphalt pavement (surface layer, base layer, and roadbed).

[0065] -asphalt- Asphalt (bituminous material) used in the bioasphalt composition may be any of, for example, straight asphalt and modified asphalt (polymer modified asphalt, semi-blown asphalt, hard asphalt).

[0066] -aggregate- The bioasphalt composition usually contains aggregate. Examples of aggregate include crushed stone, crushed rock, boulders, gravel, sand, crusher run, recycled aggregate, and ceramics. The aggregate usually contains a combination of fine aggregate and coarse aggregate. Examples of fine aggregate include aggregates with relatively small particle size (e.g., aggregates with particle size of 2.36 mm or less and 0.075 mm or more), such as river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, casting sand, and recycled aggregate crushed sand. The aggregate may be asphalt recycled aggregate (e.g., crushed and decomposed products of used asphalt). Examples of coarse aggregate include aggregates with relatively large particle size (e.g., aggregates with particle size of more than 2.36 mm), such as crushed stone. The aggregate may further contain a filler (smaller than fine aggregate, e.g., aggregates with particle size of less than 0.075 mm). The particle size of the aggregate can be measured according to the definition of particle size in JIS A5001: 1995. The weight ratio of the fine aggregate, the coarse aggregate and the filler is not particularly limited.

[0067] -Lignin components- The lignin component contained in the bioasphalt composition may be any lignin component other than a lignin derivative. For example, industrial lignins such as kraft lignin, soda lignin, soda-anthraquinone lignin, organosolv lignin, explosive lignin, lignin sulfonic acid, and sulfuric acid lignin may be used alone or in combination of two or more. Among these, kraft lignin is preferred. The raw material for lignin is usually wood, and may be any of broadleaf trees, coniferous trees, and combinations of two or more of these. The method for producing the lignin component is not particularly limited, and it may be produced by a known method.

[0068] -Components other than asphalt, aggregate, and lignin components- The bioasphalt composition may contain components other than asphalt, aggregate, and lignin components, such as fillers (e.g., stone powder), emulsifiers, solvents (e.g., water), pigments, synthetic rubber, anti-agglomerating agents, flow agents, plasticizers, electrolytes, anti-adhesion agents, and emulsifiers other than the above-mentioned compatibilizing agents.

[0069] [2.2 Usage amount] The effective amount of the compatibilizer in the bioasphalt composition (100% by weight) is usually 0.0001% by weight or more, 0.01% by weight or more, or 0.05% by weight or more, preferably 0.7% by weight or more, and more preferably 1.0% by weight or more, converted into the amount of the lignin derivative compound. The upper limit is usually 30.0% by weight or less, preferably 20.0% by weight or less, and more preferably 15.0% by weight or less.

[0070] The amount of the lignin component contained in the bioasphalt composition is usually 50% by weight or less, preferably 45% by weight or less, more preferably 45% by weight or less, based on 100% by weight of the bioasphalt. The lower limit is usually 10% by weight or more, preferably 15% by weight or more, more preferably 20% by weight or more.

[0071] The weight ratio of the compatibilizer (lignin derivative compound) to the lignin component is usually 0.001 or more, preferably 0.005 or more, more preferably 0.01 or more, and the upper limit is usually 10 or less, preferably 1 or less, more preferably 0.5 or less.

[0072] The amount of aggregate in the bioasphalt composition (100% by weight) is usually 70% by weight or more, preferably 75% by weight or more, more preferably 80% by weight or more. The upper limit is usually 97% by weight or less, preferably 95% by weight or less, more preferably 90% by weight or less. By being in the above range, the durability of the pavement laminate can be improved.

[0073] The content of asphalt is preferably 30 to 65 mass %, more preferably 35 to 65 mass %, and further preferably 40 to 65 mass %, based on the asphalt composition (100 parts by weight).

[0074] When an emulsifier is contained, the content thereof is preferably 0.1 to 15 mass %, more preferably 0.5 to 10 mass %, and even more preferably 1 to 10 mass %, relative to the asphalt composition (100% by weight).

[0075] [2.3 Manufacturing method of bioasphalt composition] The bioasphalt composition can be produced by adding each of the raw materials constituting the bioasphalt composition (asphalt, compatibilizer, lignin component, aggregate, and components used as necessary) all at once or sequentially and mixing them. Mixing is usually performed under heated conditions. The heating temperature is usually 120°C or higher, preferably 130°C or higher. The upper limit is usually 220°C or lower, preferably 200°C or lower. A preferred method for producing the bioasphalt composition is to first premix the compatibilizer and the lignin component and mix them with the remaining raw materials including asphalt. Premixing can be performed using a stirring device such as a homogenizer as necessary. In this case, it is preferable to dry the compatibilizer and the lignin component before premixing. The asphalt to which the premix is ​​added is preferably in a heated and molten state. The heating temperature in the heated and molten state is the same as above.

[0076] [2.4 Pavement] The bioasphalt composition can be used to form a pavement. A pavement generally has a laminated structure including, from the bottom up, a roadbed, a base layer, and a surface layer. A layer containing a bioasphalt emulsion composition may be formed on the surface of the surface layer, between the surface layer and the base layer, and / or between the base layer and the roadbed. Examples of methods for producing a pavement laminate include a method in which a base layer is formed on the surface of the roadbed, and a surface layer is formed on the surface of the base layer, and an example is as follows. First, a roadbed is formed by laying crushed stones, gravel, etc. on a roadbed formed by digging down the road surface and laying sand on it. The roadbed may be formed in two layers, for example, a method in which a lower roadbed is formed by laying large crushed stones, and then an upper roadbed is formed by laying relatively small crushed stones. When forming a roadbed, compaction may be performed using equipment such as a rolling vehicle as necessary. Next, a base layer is formed on the roadbed. The base layer can be formed, for example, by spreading the heated bioasphalt composition on the roadbed and compacting it using equipment such as a rolling vehicle as necessary. The surface layer is then formed on the base layer. The surface layer can be formed, for example, by spreading the heated bioasphalt composition on the base layer and compacting it using equipment such as a rolling vehicle as necessary. It is preferable to maintain a high temperature during the work of forming the base layer and surface layer. The heating temperature is usually 120°C or higher, preferably 140°C or higher. The upper limit is usually 220°C or lower, preferably 200°C or lower. When a layer containing an asphalt emulsion composition is formed, for example, after the roadbed, base layer, or surface layer is formed, the bioasphalt emulsion composition is sprayed on the layer surface, and if necessary, cured with aggregate such as sand, and the upper layer is constructed in sequence. EXAMPLES

[0077] Examples 1 to 5 and Comparative Examples 1 to 3 (1) Preparation of lignosulfonate (1-1) Preparation of lignosulfonate a-1 Wood derived from Radiata pine was treated with sulfite at 140°C and pH2 for 3 hours using magnesium sulfite solution with SO2 concentration of 4g / 100mL based on the sulfite cooking method, and sodium hydroxide solution was added to the obtained composition so that the solid content was 9wt%, and the mixture was kept at 90°C for 4 hours. Next, oxygen was blown in for 2 hours for oxygen treatment, and the pH was adjusted to 7.0, and spray-dried with a spray dryer to obtain a powder of lignin sulfonate a-1. (1-2) Preparation of lignosulfonic acid a-2 Wood derived from Radiata pine was treated with sulfite at 140°C and pH 2 for 3 hours using a magnesium sulfite solution with a SO2 concentration of 4 g / 100 mL based on the sulfite cooking method, and the resulting composition was filtered, and the filtrate was adjusted to pH 5.0 with an aqueous sodium hydroxide solution and spray-dried in a spray dryer to obtain a powder of lignin sulfonate a-2. (1-3) Preparation of lignosulfonate a-3 Wood derived from Radiata pine was treated with sulfite at 140°C and pH 2 for 3 hours using a magnesium sulfite solution with a SO2 concentration of 4 g / 100 mL based on the sulfite cooking method, and the resulting composition was filtered, and the filtrate was adjusted to pH 5.0 with an aqueous sodium hydroxide solution, concentrated using a polysulfone-based ultrafiltration membrane with a molecular weight cutoff of 20,000, and spray-dried using a spray dryer to obtain a powder of lignin sulfonate a-3.

[0078] (2) Preparation of lignin derivatives (2-1) Preparation of lignin derivative compound-1 In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, and a dropping device, 212 g of water, 90 g of lignin sulfonic acid a-1 as compound (i), 124 g of poly(ethylene oxide) monophenyl ether (average addition mole number of ethylene oxide 50) as compound (ii), 17 g of 37% formaldehyde aqueous solution, 74 g of 72% sulfuric acid aqueous solution, and 0.05 g of Pronal 753 (manufactured by Toho Chemical Co., Ltd.) as a defoamer were added, and the mixture was stirred while heating and kept at 105 ° C. for 3 hours to complete the reaction. To the resulting aqueous solution, 140 g of 250 g / L calcium hydroxide aqueous solution was added to the reaction vessel, and after stirring for 1 hour, the mixture was filtered to remove the gypsum generated by neutralization, and then the pH was adjusted with a sodium hydroxide aqueous solution to obtain a liquid of lignin derivative compound-1 containing a copolymer having a weight average molecular weight of 47,600. This liquid was dried at 140° C. using a drum dryer (manufactured by Katsuragi Kogyo Co., Ltd.) and then pulverized using an extreme mill to obtain a dried product of lignin derivative compound-1. The weight ratio of each structural unit contained in the obtained lignin derivative compound-1 was (I) / (II)=42 / 58, and the reaction rate of the aromatic water-soluble compound was 77%. The peak area ratio of the high molecular weight component of the obtained lignin derivative compound-1 was 90%.

[0079] (2-2) Preparation of lignin derivative compound-2 In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, and a dropping device, 200 g of water, 30 g of lignin sulfonate a-1 as compound (i), 70 g of poly(ethylene oxide) monophenyl ether (average molar number of ethylene oxide added: 25) as compound (ii), 10 g of 37% formaldehyde aqueous solution, 40 g of 72% sulfuric acid, and 0.05 g of Pronal 753 (manufactured by Toho Chemical Co., Ltd.) as a defoamer were added, and the mixture was stirred while being heated, and the reaction was completed by keeping the mixture at 105 ° C. for 10 hours. 80 g of 250 g / L calcium hydroxide aqueous solution was added to the obtained aqueous solution, and after stirring for 1 hour, the resulting gypsum was removed by filtration, and the pH was adjusted with an aqueous sodium hydroxide solution to obtain a liquid of lignin derivative compound-2.

[0080] This lignin derivative compound was dried at 140° C. using a drum dryer and then pulverized using an extreme mill to obtain a dried product of lignin derivative 2.

[0081] The weight ratio of each constituent unit contained in the obtained lignin derivative compound-2 was (I) / (II) = 30 / 70, the peak area ratio of the high molecular weight components was 94%, the reaction rate of compound (i) with compound (ii) was 80%, and the weight average molecular weight of the lignin derivative compound-2 was 55,000.

[0082] (2-3) Preparation of lignin derivative-3 In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, and a dropping device, 305 g of water, 25 g of lignin sulfonate a-3 as compound (i), 37 g of poly(ethylene oxide) monophenyl ether (average addition mole number of ethylene oxide 47 moles) as compound (ii), 6 g of 37% formaldehyde aqueous solution, 22 g of 72% sulfuric acid aqueous solution, and 0.02 g of Pronal 753 (manufactured by Toho Chemical Co., Ltd.) as a defoamer were added, and the mixture was stirred while being heated, and the reaction was completed by maintaining at 105 ° C for 16 hours. To the obtained aqueous solution, 45 g of 250 g / L calcium hydroxide aqueous solution was added to the reaction vessel, and after stirring for 1 hour, the mixture was filtered to remove the gypsum generated by neutralization, and then the pH was adjusted with a sodium hydroxide aqueous solution to obtain a liquid of lignin derivative 3 containing a copolymer having a weight average molecular weight of 114,000.

[0083] The weight ratio of each structural unit contained in the obtained lignin derivative-3 was (I) / (II)=40 / 60, and the reaction rate of the aromatic water-soluble compound was 82%. The peak area ratio of the high molecular weight component of the obtained lignin derivative 4 was 97%.

[0084] (2-4) Preparation of lignin derivative-4 In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, and a dropping device, 90 g of water, 75 g of poly(ethylene oxide) monophenyl ether (average number of moles of ethylene oxide added: 37) as compound (ii), 198 g of Sunflow RH (lignin sulfonate, manufactured by Nippon Paper Industries Co., Ltd.) as compound (i), 10 g of 37% aqueous formaldehyde solution, and 61 g of 72% aqueous sulfuric acid solution were added, and the mixture was stirred while being heated, and the reaction was completed by holding at 105 ° C for 3 hours. To the resulting aqueous solution, 127 g of 250 g / L aqueous calcium hydroxide solution was added to the reaction vessel, and after stirring for 1 hour, the mixture was filtered to remove the gypsum generated by neutralization. Thereafter, the pH was adjusted with an aqueous sodium hydroxide solution to obtain a liquid of lignin derivative-4 containing a copolymer having a weight average molecular weight of 29,500. The weight ratio of each of the structural units contained in the obtained lignin derivative-4 was (I) / (II)=50 / 50, and the reaction rate of the water-soluble aromatic compound was 59%.

[0085] The peak area ratio of the high molecular weight component of the obtained lignin derivative-4 was 87%.

[0086] (3) Kraft lignin The following kraft lignins were used in the tests: (3-1) West Fraser (3-2) Domtar

[0087] (4) Preparation of asphalt samples Using a dryer, the dried products of the lignin derivative compounds-1 and 2 obtained in (2), the kraft lignin described in (3), and the lignin sulfonate a-1 obtained in (1) were dried under conditions of 115°C x 2 hours. Then, 60-80 straight asphalt was heated to 150°C, and while stirring with a homomixer, the lignin derivative compound and kraft lignin after removing moisture, and the powder of the lignin sulfonate were added at the addition rates shown in Table 1. After the entire amount was added, it was stirred with a homomixer under conditions of 1 hour x 5000 rpm. On the other hand, the liquid of lignin derivative 3 or 4 was added together with kraft lignin to 60-80 straight asphalt heated to 150°C in the amounts shown in Table 1. The water was evaporated while stirring with a homomixer, and the mixture was stirred for 1 hour at 5000 rpm.

[0088] (5) Evaluation test Each of the resulting asphalt samples was subjected to the following tests.

[0089] -torque- The asphalt sample (150°C) was cooled to 100°C, and the torque was measured with a torque driver (half a rotation in 6 seconds). Three measurements were taken, and the average value was used as the torque value.

[0090] - Peeling area rate (marble coating test) - The asphalt sample was heated to 150°C, a marble (approximately 15mm in diameter, measured with a vernier caliper) was placed in it, and the asphalt sample was allowed to spread for 30 minutes, after which the marble was removed with tweezers and allowed to cool naturally. Pure water was placed in a disposable cup (enough to completely immerse the marble) and heated to 80°C, after which the marble with the asphalt spread on it was placed in and heated for 3 minutes. The marble was removed, allowed to dry naturally, and the peeled area was measured.

[0091] -viscosity- The asphalt sample after stirring at 150°C was transferred to an oil bath set at 102°C and cooled until the asphalt temperature reached approximately 97°C. Once the temperature had stabilized, the viscosity of the asphalt sample was measured at a shear rate of 141.6 1 / s using a soft solid tester (manufactured by Brookfield) with a blade-type spindle (VT-40-20).

[0092] - Compatibility evaluation - The compatibility of the asphalt samples was evaluated by checking whether or not there were any visible lumps when the bio-asphalt was stirred at 150°C for 1 hour and poured into a vat. 〇: No lumps, ×: There are lumps

[0093] [Table 1]

[0094] (Table 1 footnotes) *The kraft lignin addition rate and the compatibilizer addition rate are the ratio (wt%) of the amount added to the total amount of kraft lignin, compatibilizer, and asphalt added, which is 100 wt%.

[0095] Compared with the samples of Comparative Examples 2 and 3, which did not contain a compatibilizer, the samples of Examples 1 to 8 had smaller peeled areas and lower viscosities. The samples of Examples 1 to 8 also had smaller torque values ​​than Comparative Example 2, and were equal to or less than the sample of Comparative Example 1, which did not contain kraft lignin. Among them, the samples of Examples 4 to 8 showed lower torque values ​​than the sample of Comparative Example 1.

[0096] These results show that the compatibilizer of the present invention can improve the compatibilization of the lignin component and asphalt in bioasphalt and can achieve viscosity reduction.

Claims

1. A compatibilizer for a bioasphalt composition comprising a lignin derivative compound containing the following structural units (I) and (II): (I): Structural unit derived from lignin-based compound (II): A structural unit derived from an aromatic water-soluble compound that contains at least an aromatic water-soluble compound having an alkylene oxide chain.

2. The agent according to claim 1 , wherein the aromatic water-soluble compound having an alkylene oxide chain comprises an aromatic water-soluble compound having an alkylene oxide chain with an average added mole number of 25 or more of alkylene oxide.

3. 3. The agent according to claim 1 or 2, wherein the weight ratio (I) / (II) of the structural unit (I) to the structural unit (II) is 1 / 99 to 99 / 1.

4. A bioasphalt composition comprising asphalt, kraft lignin, and the agent of claim 1 or 2.

5. The composition according to claim 4, wherein the content of the agent according to claim 1 or 2 is 0.05 to 10% by weight based on 100% by weight of the bioasphalt composition.

6. A method for producing the bioasphalt composition according to claim 4, comprising a step of premixing the agent according to claim 1 or 2 with kraft lignin and mixing the premix with a raw material containing asphalt in a heated and molten state.

Citation Information

Patent Citations

  • Method for producing asphalt composition

    JP2021195433A

  • Lignin derivative compounds and uses thereof

    JP7154217B2

  • Asphalt composition manufacturing method and asphalt mixture manufacturing method

    WO2022085641A1